Dialectical rhetoric - McComiskey, Bruce, 1963- (Utah State University Press, 2015)
In Dialectical Rhetoric, Bruce McComiskey argues that the historical conflict between rhetoric and dialectic can be overcome in ways useful to both composition theory and the composition classroom. Historically, dialectic has taken two forms in relation to rhetoric. First, it has been the logical development of linear propositions leading to necessary conclusions, a one-dimensional form that was the counterpart of rhetorics in which philosophical, metaphysical, and scientific truths were conveyed with as little cognitive interference from language as possible. Second, dialectic has been the to.